2017
DOI: 10.1007/s11910-017-0729-y
|View full text |Cite
|
Sign up to set email alerts
|

Migraine and Stroke: What’s the Link? What to Do?

Abstract: Migraine and stroke are common, disabling neurologic disorders, with a high socioeconomic burden. A link between them has been proposed years ago, and various theories have been proposed to explain this bidirectional relation. However, the precise causes remain unclear. We briefly summarize existing hypotheses of this correlation seeking for recommendations for stroke prevention in migraineurs, if any exist. Among the strongest suggested theories of migraine–stroke association are cortical spreading depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
35
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 113 publications
1
35
0
3
Order By: Relevance
“…Although several studies provide conflicting results regarding the safety of triptans, experts do believe that their effectiveness indicates they should be considered as a treatment option for all individuals with migraine because there are no other acute migraine medications that are safe to prescribe to migraine patients with cardiovascular risk factors [15]. For example, the U.S. Food and Drug Administration issued warnings regarding the association of NSAIDs and increased risk of heart attack and stroke, and a study published in 2016 [16] reported that prescription opiates can increase the risk of coronary heart disease and cardiovascular death.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies provide conflicting results regarding the safety of triptans, experts do believe that their effectiveness indicates they should be considered as a treatment option for all individuals with migraine because there are no other acute migraine medications that are safe to prescribe to migraine patients with cardiovascular risk factors [15]. For example, the U.S. Food and Drug Administration issued warnings regarding the association of NSAIDs and increased risk of heart attack and stroke, and a study published in 2016 [16] reported that prescription opiates can increase the risk of coronary heart disease and cardiovascular death.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the report that females with migraine with aura have a higher risk of systemic ischemic complications such as stroke. 39 The pathophysiology of the relationship between gender and ischemia in migraine is not fully understood, but may be related to the effect of estrogen and progesterone on endothelial cells. 40 …”
Section: Discussionmentioning
confidence: 99%
“…3 Migraine with aura is a well-documented risk factor of acute stroke. 4 The increased incidence of atrial fibrillation and cardioembolism in patients diagnosed with migraine with aura was linked to acute stroke. 5,6 Migraine with aura can also be found as a stroke mimic during acute stroke management 7 ; however, only a few studies investigated the frequency and characteristics of migraine with aura in patients who initially presented with strokelike symptoms.…”
mentioning
confidence: 99%
“…10 Cortical spreading depression, a pathophysiological mechanism of migraine with aura, occurs rather frequently in patients with ischemic stroke. 4 Recent studies showed that migraine with aurainduced stroke may be associated with an increased risk of incidental atrial fibrillation and cardioembolic stroke. 5,6 Because we included patients diagnosed with migraine with aura who initially presented with stroke-like symptoms, all patients underwent ECG and multimodal CT scan, and more than half patients underwent DWI MRI.…”
mentioning
confidence: 99%